2000 IEEE MTT-S International Microwave Symposium Digest (Cat. No.00CH37017)
DOI: 10.1109/mwsym.2000.862367
|View full text |Cite
|
Sign up to set email alerts
|

2 GHz band even harmonic type direct conversion receiver with ABB-IC for W-CDMA mobile terminal

Abstract: A 2GHz band even harmonic type direct conversion receiver (EH-DCR) is proposed for the W-CDMA mobile terminal. Because of the well-matched antiparallel diode pair used in proposed EH-DCR, the proposed receiver can reduce even order mixing products that degrade sensitivity characteristics. Also the proposed EH-DCR can achieve low current consumption with a passive mixer approach. In this paper, the overall receiver with a RF block, an analog baseband IC (ABB-IC) and a demodulator is demonstrated to indicate eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Cohn et al and Schneider et al analyzed the harmonic mixing with APDP and demonstrated it has only even-harmonic mixing products in the form of symmetric conduction periods [7], [10]. The EHMs with APDP have been proposed for many applications such as modulators [11], [12], millimeter-wave image-rejection mixers [13], direct conversion mixers [14], [15] as well as millimeter-wave mixers [16], [17]. In this paper, using EHMs based on a pair of APDPs, the direct conversion circuitry is realized to provide both I/Q phase channels.…”
Section: Integrated Antenna With Direct Conversion Circuitrymentioning
confidence: 99%
“…Cohn et al and Schneider et al analyzed the harmonic mixing with APDP and demonstrated it has only even-harmonic mixing products in the form of symmetric conduction periods [7], [10]. The EHMs with APDP have been proposed for many applications such as modulators [11], [12], millimeter-wave image-rejection mixers [13], direct conversion mixers [14], [15] as well as millimeter-wave mixers [16], [17]. In this paper, using EHMs based on a pair of APDPs, the direct conversion circuitry is realized to provide both I/Q phase channels.…”
Section: Integrated Antenna With Direct Conversion Circuitrymentioning
confidence: 99%
“…It seems that especially the need for high integration restricts the receiver architecture to the zero-IF structure. Examples can be found in [21], [22], [23] and [24]. Al1 these receivers are designed using standard BiCMOS processes.…”
Section: Rfics For Umts: Current Developmentsmentioning
confidence: 99%
“…In order to reduce the LO self-mixing and IM2 problems normally associated with direct conversion receivers, even harmonic mixers have been implemented previously using a well-matched anti-parallel diode pair [3]- [4] or an emitter-coupled bipolar junction transistor pair [SI. In this paper, a 2GHz even harmonic mixer achieves similar performance using a standard digital CMOS technology that is more amenable to emerging system-onchip solutions.…”
Section: Introductionmentioning
confidence: 99%